In Vitro Evaluation of the Anti-Chikungunya Virus Activity of an Active Fraction Obtained from Euphorbia grandicornis Latex - José Angel Santiago-Cruz; Araceli Posadas-Mondragón; Angélica Pérez-Juárez; Norma Estela Herrera-González; José Miguel Chin-Chan; Joab Eli Aguilar-González; José Leopoldo Aguilar-Faisal (Viruses)
Chikungunya virus (CHIKV) is classified as a pathogen with the potential to cause a pandemic. This situation becomes more alarming since no approved drug exists to combat the virus. The present research aims to demonstrate the anti-CHIKV activity of molecules present in the latex of Euphorbia grandicornis. Therefore, a biodirected assay was carried out to find the molecules with anti-CHIKV activity. Extractions with hexane, dichloromethane, and methanol and subsequent purification by column chromatography were carried out to later evaluate cytotoxic activity by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay and antiviral activity by plaque assay. Our findings show that unlike the others, methanolic extract has a low cytotoxic effect and a good anti-CHIKV effect (EC50 = 26.41 µg/mL), which increases when obtaining the purified active fraction (pAFeg1) (EC50 = 0.4835 µg/mL). Time-of-addition suggests that the possible mechanism of action of pAFeg1 could be inhibiting any of the non-structural proteins of CHIKV. In addition, both the cytotoxic and anti-CHIKV activity of pAFeg1 demonstrate selectivity since it killed cancer cells and could not inhibit DENV2.